2004
DOI: 10.1007/s00269-004-0409-8
|View full text |Cite
|
Sign up to set email alerts
|

Semi-empirical Gibbs free energy formulations for minerals and fluids for use in thermodynamic databases of petrological interest

Abstract: The P-T partition function in statistical thermodynamics can be used to derive semi-empirical formulations of the Gibbs free energy G for minerals and fluids. Parameterization of these equations includes simultaneous regression of experimental heat capacity and molar volume data, allowing fitting, appraisal and optimization of various data sources, as required in the construction of internally consistent petrological data bases. This approach can also be extended to minerals with k-transitions and to fluids by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(17 citation statements)
references
References 67 publications
2
15
0
Order By: Relevance
“…Our calculations have also shown a similar strong positive correlation between isothermal silica solubility and the degree of association or clustering of H 2 O molecules in pure H 2 O ( Fig. 1c), which increases with increasing density (e.g., Gorbaty & Kalinichev, 1995;Luck, 1980;Gerya & Perchuk, 1997;Gerya et al, 2004). This strongly suggests that the dissolution of silica is directly related to the actual proportion of associated (i.e., clustered, "liquid-like") H 2 O molecules in the aqueous fluid, and offers the possibility of deriving a general thermodynamic description for silica solubility in water.…”
Section: Thermodynamic Formalismsupporting
confidence: 72%
See 2 more Smart Citations
“…Our calculations have also shown a similar strong positive correlation between isothermal silica solubility and the degree of association or clustering of H 2 O molecules in pure H 2 O ( Fig. 1c), which increases with increasing density (e.g., Gorbaty & Kalinichev, 1995;Luck, 1980;Gerya & Perchuk, 1997;Gerya et al, 2004). This strongly suggests that the dissolution of silica is directly related to the actual proportion of associated (i.e., clustered, "liquid-like") H 2 O molecules in the aqueous fluid, and offers the possibility of deriving a general thermodynamic description for silica solubility in water.…”
Section: Thermodynamic Formalismsupporting
confidence: 72%
“…This strongly suggests that the dissolution of silica is directly related to the actual proportion of associated (i.e., clustered, "liquid-like") H 2 O molecules in the aqueous fluid, and offers the possibility of deriving a general thermodynamic description for silica solubility in water. It has been shown recently (Gerya & Perchuk, 1997;Gerya et al, 2004) that from the viewpoint of thermodynamics pure H 2 O fluid (and many other gases) can be effectively treated as a mixture of molecules in two distinct states:…”
Section: Thermodynamic Formalismmentioning
confidence: 99%
See 1 more Smart Citation
“…5 -1.0 GPa. An alternative approach is to treat H 2 O in terms of a statistical thermodynamic model involving a dynamic equilibrium between "gas-like" disordered and "liquid-like" clustered molecules (Gerya and Perchuk, 1997;Gerya et al, 2004), where X(liq) is the mole fraction of the latter. Gerya et al (2005) successfully tested this approach for SiO 2 -H 2 O solutions to 1300°C and 2 GPa.…”
Section: The Ordovician Galiñeiro Peralkaline Gneiss Complex Vigo Nmentioning
confidence: 99%
“…X H 2 O has been calculated assuming all salts are fully associated under all conditions. Gerya & Perchuk (1997) and Gerya et al (2004) have shown that pure H 2 O can be treated as a solution of molecules in (1) "liquid-like" (clustered) state, and (2) "gas-like" (free) state. Quartz solubility in H 2 O -CO 2 fluids is almost as ideal, with a solvation number of 3.5.…”
Section: Referencementioning
confidence: 99%